LINKING GREEN SCEPTICISM TO GREEN PURCHASE INTENTION - Jenny E.P. Chuah; Say Keat Ooi; Jasmine A.L. Yeap, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The increased awareness on climate change and various environmental problems has induced consumers’ eco-friendly or green purchase intention. However, the perceptions that firms are disseminating inaccurate or confusing green information (greenwashing) have increased customer scepticism about environmentally friendly or green claims. The link between green scepticism and consumers’ intention to buy green products remained unclear. This paper aims to address this lacuna by thoroughly examining the attribution formation, motives and outcome of green scepticism based on the attribution theory. Overall, this comprehensive model advances valuable insights for marketers seeking to understand the conceptually distinct nature of green scepticism and consumer green purchase intention. In a nutshell, this study charts future prospects for green marketing research and presents a number of theoretical and practical significances for business practitioners and marketing scholars.